2000
DOI: 10.1097/00006534-200002000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Segmental Neuromuscular Stimulation: An Effective Approach to Enhance Fatigue Resistance

Abstract: Electrical stimulation of skeletal muscle flaps is used clinically in applications that require contraction of muscle and force generation at the recipient site, for example, to assist a failing myocardium (cardiomyoplasty) or to reestablish urinary or fecal continence as a neo-sphincter (dynamic graciloplasty). A major problem in these applications (muscle fatigue) results from the nonphysiologic manner in which most of the fibers within the muscle are recruited in a single burst-like contraction. To circumve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…This type of spatially distributed and sequentially applied stimulation is referred to as ‘sequential stimulation’ (Nguyen et al 2011). Fatigue was reduced with such stimulation in animal experimental models using spinal stimulation (Petrofsky 1978, 1979; Mushahwar and Horch 1997), intrafascicular stimulation (McDonnall et al 2004; Yoshida and Horch 1993), interfascicular stimulation (Thomsen and Veltink 1997), epineural stimulation (Petrofsky 1979), and intramuscular stimulation (Lau et al 1995; Zonnevijlle et al 2000; Lau et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…This type of spatially distributed and sequentially applied stimulation is referred to as ‘sequential stimulation’ (Nguyen et al 2011). Fatigue was reduced with such stimulation in animal experimental models using spinal stimulation (Petrofsky 1978, 1979; Mushahwar and Horch 1997), intrafascicular stimulation (McDonnall et al 2004; Yoshida and Horch 1993), interfascicular stimulation (Thomsen and Veltink 1997), epineural stimulation (Petrofsky 1979), and intramuscular stimulation (Lau et al 1995; Zonnevijlle et al 2000; Lau et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…[18,38] Nevertheless, other researchers have also used a threshold of 50%. [34,39,40] Because In the present results, at lower levels of injected PA×PD, a low signal-to-noise ratio combined with low security in torque production resulted in low bilateral symmetry (see Table 1) and higher sensitivity to measurement error (e.g., when low torque levels [< 10 Nm] are generated in Figure 3). However, our measurement precision was sufficiently high at higher levels of injected PA×PD, where both torque production and fatigue were substantial that has higher clinical relevance.…”
Section: Limitations 431 Choice Of Muscle Fatigue Indexmentioning
confidence: 41%
“…However, studies comparing asynchronous to conventional stimulation have primarily focused on isometric contractions with fixed stimulation parameters [21]- [25], [28]- [32], [34], due to the fact that it is easier to control for variation in the data. Sequential stimulation has also been shown to be advantageous over conventional stimulation as a method to reduce fatigue in isometric contractions [36], [37]. However, one study [36] found that a shorter on-time (i.e., the time to keep one stimulation channel activated before switching to the next channel) resulted in less fatigue, motivating the use of asynchronous stimulation over sequential stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…focused on isometric contractions with fixed stimulation parameters (i.e., open-loop stimulation) [21]- [25], [28]- [32], [34], [36], [37]. Therefore, it is presently unclear if the fatigue benefits reported for open-loop stimulation similarly applies to feedback control of NMES in man.…”
Section: Introductionmentioning
confidence: 99%